Telling the Civil War in Nikolai Aseev's Semën Proskakov. Issue 1 (2nd January 2019) - Rewinski, Zachary
Abstract : The ten-year anniversary of the October Revolution in 1927 was celebrated across Soviet society, but scholarship on the anniversary lacks detailed analysis of the literary contributions to the celebration. This article presents analysis of Nikolai Aseev's 1927 poema (narrative poem) Semën Proskakov in terms of its relation to the anniversary and ongoing attempts to formulate memory of the revolutionary past. It treats the poema as a narrative of the civil war told partially through accounts of actual participants and partially as a fictionalized rendition of these stories. Highlighting adherence to and deviation from source material, the article argues that while the Lef theory of factography provided a basis for Aseev's narration of the civil war, it did not preclude inscription of historical figures into literary paradigms prevalent in Soviet literature at the time.